PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI, DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR KARYAWAN - Putri, I Gusti Ayu Ambalika; Suwandana, I Gusti Made (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of transformational leadership style, compensation and organizational commitment on organizational citizenship behavior (OCB) employees at the Civil Servants Cooperative Bina Sejahtera Badung regency. This research was conducted at the Civil Servants Cooperative Bina Sejahtera Badung engaged in micro-credit and store business unit with a sample of 61 respondents (Sample Saturated) .Teknik wear multiple linear regression analysis. The results of analysis that transformational leadership style significant positive effect on organizational citizenship behavior (OCB) employees at the Civil Servants Cooperative Bina Sejahtera Badung regency. Compensation significant positive effect on organizational citizenship behavior (OCB) employees at the Civil Servants Cooperative Bina Sejahtera Badung regency. Organizational commitment significant positive effect on organizational citizenship behavior (OCB) employees at the Civil Servants Cooperative Bina Sejahtera Badung regency. Advice can be given, the company should be willing to foster employee survive in company with the provision of financial benefits that fit employees' workload.
Keywords: transformational leadership, compensation, organizational commitment on organizational citizenship behavior (OCB)